“MELESTARIKAN EKOSITEM DARAT MELALUI SDGS 15” PENGEMBANGAN MEDIA ANIMASI EDUKATIF UNTUK MENDUKUNG PEMBELAJARAN BERBASIS SDGS 15 DI SEKOLAH DASAR - Winas Kailola Inkiriwang, Ara; Putri Rahmi Haerani , Rosita; Suhartini , Erna; Asrafiani Arafah , Andi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The issue of environmental preservation has become a global concern that must be instilled from an early age, including through primary education. However, the implementation of sustainability-based learning, such as SDG 15 (Life on Land), remains limited at the elementary school level.This research aims to develop SDG 15-based animation teaching media for Grade V students using Eleven Labs and Adobe Express Animation. The research instruments include questionnaires, interviews, and observations, while data collection techniques involve validation by subject matter and media experts, as well as small- and large-group trials. The study adopts the Research and Development (R&D) method with the ADDIE model, which consists of analysis (needs, student characteristics, and curriculum), storyboard design, animation development, implementation, and evaluation.The research findings indicate that the media received a "highly feasible" category from subject matter experts (92.19%) and media experts (94.79%). Trials conducted with Grade V students showed an improvement in understanding land ecosystems and environmental awareness, with student response scores reaching 84.55%. This media is considered effective in enhancing learning motivation, material relevance, and students' comprehension of environmental sustainability.